Research on the Development Model of Cross Border Kazakh Ethnic Cultural Tourism - SEKEN, Aday; MAZBAYEV, Ordenbek; AGYBETOVA, Rina; AKIMOV, Zhaxylyk; TLEUBAYEVA, Aitolkyn (Journal of Environmental Management and Tourism, 2019)
Spatial distribution, cultural system and characteristics, constitution of ethno-cultural tourism resources of global Kazakh ethnics was examined in this study, as well as spatial distribution of transnational ethno-cultural tourism resources, and development state and existing problems of Kazakh ethno-cultural domestic and international tourism. Based on the analysis above, ten development patterns of Kazakh ethno-cultural tourism were raised up, including ethnic village, ethnic cultural museum, primitive ethnical village, conformity of relics, conformity and improvement, renew of old fashion and customs, new rural construction, special town construction, ethnic cultural recreational-business district (RBD) and ethnic cultural thematic parks. Further, reasonable regional functions and spatial development pattern of Kazakh ethnic cultural tourism in Xinjiang were discussed, providing foundations for new theories and studies of the industrial development of ethnic cultural tourism in Xinjiang.